Cellulose nanocrystals of variable sulfation degrees can sequester specific platelet lysate-derived biomolecules to modulate stem cell response. Issue 50 (21st May 2020) - Mendes, Bárbara B.; Gómez-Florit, Manuel; Osório, Hugo; Vilaça, Adriana; Domingues, Rui M. A.; Reis, Rui L.; Gomes, Manuela E.
Abstract : Cellulose nanocrystals can bind different patterns of platelet lysate-derived protein in a surface sulfation dependent manner. The potential to direct stem cell fate by solid-phase presentation of defined protein coronas is demonstrated. Abstract : The surface chemistry of cellulose nanocrystals was engineered to show variable sulfation degrees, which was exploited to modulate platelet lysate-derived biomolecule sequestration and presentation. The protein coronas developed on CNC surfaces were characterized and it was demonstrated how they promote different signaling effects on human adipose-derived stem cell behavior.